Advantages of Using Innovative Technologies in the Development of Student Speech - Salohiddinova Nigora Inomjonovna; Madaminova Shoira; Holmatova Gulbodom; Tursunboyeva Karomatxon (Zien Journals, 2022)
This article discusses the advantages of using innovative technologies in the development of student speech. It is also important that the teacher should present each lesson as a product of creativity, while ensuring the interest of students in the Uzbek language on the basis of modern pedagogical technologies, the development of consistent speech is one of the main components of educating students discussed. Because one of the urgent tasks of teaching the Uzbek language is to form a free and independent thinker, a conscious and active participant in socio-political life. The development of such individuals will allow the introduction of the foundations of democracy in the socio-political life of the country, as well as a full understanding of the duties and responsibilities of civil society and the acceleration of the rule of law.
Keywords: speech; linguistics; pedagogical technology; innovation